`Keeping us from breaking`: elite athletes' access to and use of complementary and alternative medicine - Bundon, A. M.; Hurd Clarke, L. C. (Qualitative Research in Sport, Exercise and Health, 2014)
This paper draws on in-depth interviews with 12 female members of Canadian national sport teams to investigate the factors that encourage and delimit their use of complementary and alternative medicine (CAM). We investigate how CAM treatments are promoted and subsidised within the structures of the Canadian sport system, including via the Athlete Assistance programme (monthly stipend paid to national team members). Our findings suggest that an athlete's decision to try CAM is contingent on her conformity to the sport ethic, her existing health beliefs and norms pertaining to CAM usage within her sport. We propose that in order to more fully meet the needs of the athletes and maximise the potential benefits of CAM, a more reflective and critical approach to how and when these services are provided to high-performance athletes is necessary. We discuss our findings in light of Andersen's Behavioural Model that describes an individual's use of health services as the result of predisposing and enabling factors as well as the need for care.